Imperfect law enforcement, informality, and organized crime - Lara Miguel A. Mascarúa (Banco de México, 2022)
How does imperfect law enforcement affect drug trafficking, predation on firms, informality, and aggregate production? To quantify it, a general equilibrium occupational model is developed in which there is room for drug trafficking, crime against businesses, and tax evasion in the presence of imperfect institutions. Detailed micro-level data on business victimization and cartels in Mexico are used to calibrate the model. It is found that the imperfect application of the law generates considerable losses in production derived from a misallocation of occupations and resources. Finally, using counterfactual simulations, the effects of policies that seek to improve the allocation of resources are calculated. With complete law enforcement in the illegal drug market, the workers in that sector would relocate to the productive sector, and aggregate production would increase. Without crimes against businesses, which would allow a reallocation of work, capital, and occupations to the formal sector, production would increase even more. However, the largest effects come from a decrease in informality.
Keywords: O11; O17; O43; O47; K42; 330; Misallocation; aggregate distortions; drug cartels; crime; formal and informal sectors